KONSEP DALAM PENJAMINAN MUTU PENDIDIKAN AGAMA ISLAM DISEKOLAH MENENGAH PERTAMA DI INDONESIA - Ghozali; Romi Faslah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational quality assurance is a fundamental component of the national education system, ensuring that learning processes and outcomes meet established quality standards. In the context of Islamic Religious Education PAI in Junior High Schools SMP, quality assurance encompasses a broader dimension than simply academic achievement. It also encompasses the development of students' religious character, morality, and spiritual values ​​as part of the holistic goals of Islamic education. Therefore, PAI quality assurance requires alignment between planning, implementation, evaluation, and follow-up to achieve learning quality. This study employed a descriptive qualitative approach with a content analysis method that focused on the study of concepts, policies, and implementation of the PAI quality assurance system in SMP. Data were obtained through a literature review from various sources, including scientific books, academic journals, government regulations, and relevant previous research. The analysis process involved data reduction, presentation, and conclusion drawing to identify the link between education quality policies and their implementation in schools. The study results show that Islamic Religious Education PAI quality assurance requires functional synergy between Islamic Religious Education PAI teachers, principals, supervisors, and educational quality assurance institutions to ensure effective and targeted learning. With the implementation of a planned and sustainable quality assurance system, Islamic Religious Education PAI education in junior high schools has great potential to shape a generation that is not only intellectually superior but also possesses strong moral and spiritual integrity. The synergy between spiritual, pedagogical, and managerial aspects is the main foundation for realizing quality Islamic religious education that is relevant and adaptive to the challenges of the times. Therefore, strengthening the Islamic Religious Education PAI quality assurance system must be a strategic priority in national education development to produce students who are faithful, have noble character, and are competitive in the global era.